تحليل أخطاء القراءة الجهرية لدى طلبة المدارس الثانوية الحكومية بماليزيا: الإعراب نموذجا - Asiah binti Mat Ripin
This research studies the oral reading errors in Arabic Language among public secondary school students in Malaysia on inflection topic and its effect on understanding meaning of reading substance. The researcher relied on qualitative approach to get the desired information through oral reading interview, immediate recall protocol, test in inflection topic and test to measure comprehension and understanding of reading tools. The researcher conducted interviews with seven students from form 4 in Sekolah Menengah Kebangsaan (Agama) Wataniah, Machang Kelantan. The result showed that the most comman types of errors in inflection during oral reading in Arabic Language is nasab, followed by rafa', jar and jazam. The study also revealed that the level of used of inflection was at a average level, but tended to be weak, indicating that most of the samples obtained a medium percentage and the lowest sample was close to the level of fail. Result also showed that the level of comprehension and understanding meaning was influenced by the knowledge of inflection during reading the Arabic text.